1978
DOI: 10.1055/s-0028-1093446
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Luteinizing Hormone (LH) and Testosterone (T) or Dihydrotestosterone (DHT) in the Gonadotropic Cells of the Anterior Pituitary by using Ultracryomicrotomy and Immunocytochemistry

Abstract: On the other hand, both eel and salmon calcitonin I were inactivated less markedly and in the similar manner. The relationship between the hypocalcemic effect 01' calcitonins and the inactivation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Autoradiographic and cell separation [16][17][18] studies have demonstrated that the gonadotroph is the principle cell type which concentrates androgen. Far fewer lactotrophs and so matotrophs will concentrate androgen suggesting that the prin ciple direct action of androgen on anterior pituitary physiology is to regulate the release of gonadotropins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoradiographic and cell separation [16][17][18] studies have demonstrated that the gonadotroph is the principle cell type which concentrates androgen. Far fewer lactotrophs and so matotrophs will concentrate androgen suggesting that the prin ciple direct action of androgen on anterior pituitary physiology is to regulate the release of gonadotropins.…”
Section: Discussionmentioning
confidence: 99%
“…Based on autoradiographic and immunochemical evidence, the principle anterior pituitaiy cell type which concentrates an drogen is the gonadotroph [16][17][18], In comparison, the number of lactotrophs which concentrate radiolabelled T are small [16][17][18]. The restricted distribution of AR suggests that the ob served effects of E on AR number may be restricted to the go nadotroph.…”
mentioning
confidence: 99%
“…After washing with buffer, the specimens were postfixed for 1 h in 1% phosphate-buffered osmium tetroxide, washed again, incu bated for 30 min in 0.4 M sucrose and then frozen as described previously [6,12,14,15]. Ultrathin sections were cut at -120°C on an Ultrotome III (LKB Stockholm, Sweden) fitted with a Cryokit, as described by Tokuyasu [25].…”
Section: Methodsmentioning
confidence: 99%
“…19 589). This se rum has been studied previously [16]. Anti-porcine luteinizing hor mone (3 (pLHji) serum.…”
Section: Antiseramentioning
confidence: 99%